2021
DOI: 10.31489/2021ch2/86-95
|View full text |Cite
|
Sign up to set email alerts
|

Thermokinetic parameters of the primary coal tars destruction in the presence of catalysts and polymeric materials

Abstract: The hydrogen-donor abilities of polymers and the activity of catalysts in the process of thermal destruction of the organic mass of primary coal tar (PCT) are studied by non-isothermal kinetics methods. PCT,magnetic microspheres, nickel-deposited chrysotilechrysotile and Fe3O4nanocatalysts were used as initial raw materials. Рolymers such as polyethylene (PE), polystyrene(PS) and polyethylene glycol (PEG) were selected as a hy-drogen donor. The phases Mg3[OH]4{Si2O5} and NiO were determined by X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The conversion degree of sample 3 at a heating rate of 10 • C/min was 86 wt.% at 500 • C, whereas the conversion rate of sample 1 at the same temperature was 60 wt.% and of sample 2 was 69 wt.%. This confirmed our earlier conclusions in [36] on the thermal decomposition of a mixture of low-temperature coal vacuum residue resin with a chrysotile-based catalyst. We have found that the rate of vacuum residue thermal degradation depends on the qualitative composition added to the nanocatalyst.…”
Section: Discussionsupporting
confidence: 92%
“…The conversion degree of sample 3 at a heating rate of 10 • C/min was 86 wt.% at 500 • C, whereas the conversion rate of sample 1 at the same temperature was 60 wt.% and of sample 2 was 69 wt.%. This confirmed our earlier conclusions in [36] on the thermal decomposition of a mixture of low-temperature coal vacuum residue resin with a chrysotile-based catalyst. We have found that the rate of vacuum residue thermal degradation depends on the qualitative composition added to the nanocatalyst.…”
Section: Discussionsupporting
confidence: 92%
“…Substitutions ( 2) and (3) provide the OFW equation ( 4) to calculate how thermal breakdown rate of catalyst mixtures with LTCR depends on inverse temperature calculated the activation energy and the preexponential multiplier [15]. Thermogravimetric (TG) curves (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Equation ( 4) implies that for a series of temperature measurements of thermal degradation of lowtemperature coal tar catalyst mixtures obtained at different β heating speeds of samples and fixed values of their transformation degree α, the graph of the function lnβ = f (1/T) gives straight lines (isoconversion lines) the tangent of the inclination of which -1.052E/R is directly proportional to the activation energy [15] (Fig. 3 a-d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NiO supported on chrysotile leads to a significant reduction of activation energy in the process of thermal destruction of primary coal tar/polymeric materials mixture [14].…”
Section: Introductionmentioning
confidence: 99%